Congenital Defects in Neutrophil Dynamics - Marton Keszei; Lisa S. Westerberg (Journal of Immunology Research)
Neutrophil granulocytes are key effector cells of the vertebrate immune system. They represent 50–70% of the leukocytes in the human blood and their loss by disease or drug side effect causes devastating bacterial infections. Their high turnover rate, their fine-tuned killing machinery, and their arsenal of toxic vesicles leave them particularly vulnerable to various genetic deficiencies. The aim of this review is to highlight those congenital immunodeficiencies which impede the dynamics of neutrophils, such as migration, cytoskeletal rearrangements, vesicular trafficking, and secretion.